Revival and change : the 1957 and 1958 Diefenbaker elections - Courtney, John C. (John Childs), 1936- (Turning point elections., 2022)
"Revival and Change is a compelling account of the elections, accomplishments, challenges, failures, and ultimate end of the Diefenbaker era. The Liberals had been in office for two decades when the 1957 election was called and were widely expected to win another majority government. But it soon became clear that John Diefenbaker, the new Conservative leader, overshadowed his opponents. He seized the opportunity that television and boisterous rallies offered to denounce Liberal arrogance and to present his vision of a new Canada. He captured the mood of the country and was ultimately victorious. A second election in 1958 resulted in a landslide victory for the new Conservative Government. The Liberals were reduced to their smallest number of seats since Confederation, the CCF lost its leader and all but eight seats, and Social Credit was wiped out completely. It was a rout never before seen in Canadian history. This is the story of those elections, the government and opposition they produced, the issues that defined the government, and the era's legacy in Canadian politics and society."--